Rhizanthes lowii (Becc.) Harms. (Rafflesiaceae), a new record from Lanjak Entimau Wildlife Sanctuary, Sarawak, Malaysia - Meekiong, Kalu; Jackson, D.; Ampeng, A.; Albukharey, M. R.; Latiff, A. (Malaysian Nature Society, 2020)
Rhizanthes lowii (Becc.) Harms., a new species record from the Lanjak Entimau Wildlife Sanctuary, Sarawak is re-described and illustrated. The blooms show outstanding features that include its orange-white batik pattern half-way through every tepal with very dense hairs covering the entire inner side of the tepals. Its host is Tetrastigma diepenhorstii (Vitaceae).